Career attitudes and values of professional men and women : a life stage and career stage comparison : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Martin, Fiona (Massey University, 1994)
The present study was designed to compare the work attitudes and values of professional men and women and to relate these to two theoretical models. The intention was to determine if Levinson's (1978) and Super's (1957) models of life and career stage could account for the experiences of a sample of New Zealand professional people. Each model was tested by separate MANOVAs for any significant differences between the sexes as well as variance within respondent's work attitudes within each formulation of stages. The results indicated that there were no significant differences between the work attitudes of men and women in the research sample. Levinson's model accounted for some differences between stages on the work attitudes; "willingness to relocate", "intention to leave", and "desire for promotion". Super's model accounted for more differences between stages on the work attitudes; "intention to leave", "desire for promotion", "preferred timing for promotion", "organisational commitment", and "job involvement". There were some differences between men and women on the importance placed on certain work values across career and life stages. However, there were more similarities than differences. Across both sexes, and both life and career stages, the following work values were deemed to be important; "Intellectual Stimulation", "Achievement", "Way of Life", and "Supervisory Relations". The implications of these results are discussed in relation to previous research as well as practical implications for organisations and human resource practitioners.
Keywords: Career development; Vocational interests